Are Intoxicated Trauma Patients at an Increased Risk for Intraoperative Anesthetic Complications? A Retrospective Study - Brian D. Wolf; Swapna Munnangi; Raymond Pesso; Charles McCahery; Madhu Oad (Anesthesiology Research and Practice)
Background. The purpose of this study was to correlate intraoperative anesthetic complications of trauma patients with their respective urine toxicology results. Methods. This retrospective, single-center cohort study at a Level 1 trauma center included patients with the following criteria: (1) trauma admission between January 1, 2010, and December 31, 2016, (2) required surgical intervention, (3) are age 18 and older, and (4) urine toxicology screening was completed. Anesthetic records were evaluated for intraoperative complications. Results. The final analysis included 847 patients. The mean anesthesia time, American Society of Anesthesiologists physical status classification scores, change in body temperature, anesthetic complication rate, and mortality were not significantly different between urine toxicology positive and negative patients. Of note, a significantly lower proportion of the urine toxicology positive patients were extubated postoperatively in comparison to urine toxicology negative patients (57.32% vs 63.83%). Conclusions. Trauma patients who presented with a positive urine toxicology screening are not at an increased risk for intraoperative anesthetic complications compared to those with a negative urine toxicology screening. However, our results indicated that the need for postoperative mechanical ventilation increased in the acutely intoxicated trauma patients when compared to those without preinjury intoxication.